2010
DOI: 10.4049/jimmunol.0900439
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-Redox Balance Regulates c-rel–Driven IL-12 Production in Macrophages: Possible Implications in Antituberculosis Immunotherapy

Abstract: Material Supplementary 9.DC1http://www.jimmunol.org/content/suppl/2010/02/15/jimmunol.090043

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 59 publications
7
37
1
1
Order By: Relevance
“…Besides, it is known that interleukin IL-12 (p70) promotes the differentiation of the Th1 cells and the production of IL-2 and IFN-γ thereby supporting cellular immunity, while IL-12 (p40) acts as an antagonist of IL-12 p70 (Suzuki et al 2003;Alam et al 2010). Previous studies have reported that oxidative stress, in particular GSH status, suppresses the IL-12 (p40/p70) production resulting in a Th2 polarized immune response (Murata et al 2002a(Murata et al , 2002bKamide et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it is known that interleukin IL-12 (p70) promotes the differentiation of the Th1 cells and the production of IL-2 and IFN-γ thereby supporting cellular immunity, while IL-12 (p40) acts as an antagonist of IL-12 p70 (Suzuki et al 2003;Alam et al 2010). Previous studies have reported that oxidative stress, in particular GSH status, suppresses the IL-12 (p40/p70) production resulting in a Th2 polarized immune response (Murata et al 2002a(Murata et al , 2002bKamide et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We characterized the secretion of some SASP components in response to oxidative stress (SIPS) and proteasome inhibition induced premature senescence (PIIPS) in primary lung mice fibroblasts and compared them with SASP from replicative senescence (RS). Since the glutathione-redox balance is known to play a significant role in regulating cellular immune responses (Alam et al 2010;Reynaert 2011), GSH/GSSG ratio was determined. Our results showed that SASP profile in RS and SIPS were very similar, but both were very different from PIIPS profile.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell extracts were prepared by using lysis buffer as described earlier (42). The coimmunoprecipitated proteins were detected by Western blotting using appropriate combinations of primary and secondary Abs.…”
Section: Immunoprecipitation Assaymentioning
confidence: 99%
“…Human PBMCs obtained from Lonza (Walkersville, MD) were diluted in RPMI 1640 medium (Invitrogen) containing 10% FBS and seeded in 100-mm petri dish at a density of 20 3 10 6 cells. The MDMs were purified as described elsewhere (42).…”
Section: Cell Culturementioning
confidence: 99%
“…123. ratio is greater than 1 (>1), thus the host's immunity defense system was dominated by 124. pro-inflammation condition 26 .…”
mentioning
confidence: 99%